2010
DOI: 10.1063/1.3517492
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-phase p-type silicon oxide containing silicon nanocrystals and its role in thin-film silicon solar cells

Abstract: Lower absorption, lower refractive index, and tunable resistance are three advantages of amorphous silicon oxide containing nanocrystalline silicon grains (nc-SiOx) compared to microcrystalline silicon (μc-Si), when used as a p-type layer in μc-Si thin-film solar cells. We show that p-nc-SiOx with its particular nanostructure increases μc-Si cell efficiency by reducing reflection and parasitic absorption losses depending on the roughness of the front electrode. Furthermore, we demonstrate that the p-nc-SiOx re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 12 publications
3
96
1
Order By: Relevance
“…There have been numerous attempts to overcome this problem [22][23][24][25], but there is still lack of a complete understanding of the phenomenon. The most efficient way to overcome the problem is to use an ultrathin μc-Si:H or silicon oxide (μc-SiO:H) p-layer, which is more conducting than a hydrogenated amorphous silicon carbide (a-SiC:H) p-layer [2,4,5]. Like the TCO layer, the window layer should also exhibit high transparency and sufficient conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous attempts to overcome this problem [22][23][24][25], but there is still lack of a complete understanding of the phenomenon. The most efficient way to overcome the problem is to use an ultrathin μc-Si:H or silicon oxide (μc-SiO:H) p-layer, which is more conducting than a hydrogenated amorphous silicon carbide (a-SiC:H) p-layer [2,4,5]. Like the TCO layer, the window layer should also exhibit high transparency and sufficient conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there has been considerable interest recently in wide band gap nanostructured Si materials which may offer better performance/stability to the top cell and allow reducing the thickness of the bottom cell using enhanced light trapping techniques. These nanostructured Si materials mainly include hydrogenated amorphous and microcrystalline silicon oxide (a-and μc-SiO:H) [2][3][4][5][6][7][8], protocrystalline (pc-Si:H) [9] and polymorphous (pm-Si:H) silicon [10] that could be used as alternatives to standard doped and absorber layers, respectively. On the other hand, the light trapping is mainly realized by texturing of transparent conductive oxide (TCO) layers on glass substrates [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Since the electrical and optical parameters of the material are tunable within a wide range, 4 several other applications for solar cells have been explored. The material has been used as a transparent n-type 5 or p-type contact for heterojunction, 6,7 and thin-film silicon solar cells [8][9][10][11] or as a dielectric layer in back reflectors for a thin film single-junction 12 or doublejunction solar cells. 13 For several years, spinodal decomposition of a-SiO x layers by thermal annealing was used to fabricate silicon nanocrystals (nc-Si) in a silicon-dioxide matrix.…”
Section: Introductionmentioning
confidence: 99%
“…V oc has been successfully improved with the use of wide band gap off-stoichiometric silicon oxide as window layer in a-Si:H [7,8] and μc-Si:H single junction solar cells [9,10]. In the latter case, Cuony et al [9] attribute this improvement to the shunt quenching effect but it appears that it is not the dominant effect in the case of a-Si:H n-ip solar cells as reported by Biron et al [11].…”
Section: Introductionmentioning
confidence: 57%
“…In the latter case, Cuony et al [9] attribute this improvement to the shunt quenching effect but it appears that it is not the dominant effect in the case of a-Si:H n-ip solar cells as reported by Biron et al [11]. Other groups reported that SiOx:H layers fabricated by glow discharge deposition from a SiH 4 -CO 2 -H 2 precursor gas mixture lead to the formation of a mixed phase (MP) material in which silicon nanocrystals are embedded into an a-SiOx:H matrix [12,13], instead of an amorphous Si-O compound corresponding to the random network model (RNM) [14,15].…”
Section: Introductionmentioning
confidence: 99%